Tospovirus-Resistant Tomato Varieties for Southern Florida - Rebecca L. Wente; Samuel F. Hutton; Scott Adkins; William Turechek; Joseph E. Funderburk (EDIS, 2017)
Authors describe performance of Tospovirus-resistant tomato varieties under commercial production settings in Dade County, FL. Virus resistance has become important for this area since the emergence of two new tomato-infecting tospoviruses. Knowledge of availability and performance of resistant varieties will help growers who are looking for alternative varieties.